Estudo do comportamento térmico do rotor do motor de indução utilizando o método de elementos finitos - Dias, Felipe Aguiar (2019)
Induction motors are the most used in industrial plants. Because the high level of automatism of the plants, the incidence of trips is common, especially in the starting. Due to electromagnetics and thermal phenomena, the heating of the rotor of this kind of motors is high in the starting, justifying the need for a protection that will not let an aggressive start sequence that would cause an excessive heating. In this work a real 13.8kV, 6.1MW, 4 poles compressor drive motor was used. With some known and some estimated data, the motor was implemented in a finite element electromagnetics software. After checking the similarity between the model and the real motor (starting current, breakdown torque, nominal rotation) the losses in the rotor during the starting are calculated. The rotor losses are the main input data for the thermal analyses (also made in a finite element software), where the aim is to find heating and cooling curves of the rotor during the starting. The final objective of this work is to find first order exponential functions which best fit with the curves calculated in the thermal simulations. With the time constants of this curves is possible to parameterize protection relays that would best fulfill the compromise between protection and availability.